RIBA DALAM PANDANGAN AL-QUR’AN DAN HADIS - FITRI SETYAWATI (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2017)
Riba in The View of Al-Qur'an And Hadis. usury is an exploitation activity and doesnot use the concept of ethics or morality. The problem forbids transactions thatcontain elements of ribawi, this is due mendholimi others and the element of injustice(unjustice). The scholars agreed and stated firmly about the prohibition of usury.Broadly usury riba there are two namely: usury due to debt accounts receivable andusury due to sale and purchase.